HOW E-COMMERCE IS TRANSFORMING INTERNATIONAL TRADE - Ortigaliyev Ulugbek (Modern American Journals, 2025)
The growth of e-commerce is significantly transforming international trade by breaking down traditional barriers and opening up global markets to businesses of all sizes. Online platforms such as Amazon, Alibaba, and various regional players have made cross-border transactions faster, more affordable, and more accessible than ever before. This article explores the key factors behind this shift, including technological advancements, digital payment innovations, and the evolution of logistics systems. It also considers the broader implications for businesses, consumers, and policymakers as global trade becomes increasingly digital. Using real-world examples and current data, the article illustrates how e-commerce is reshaping the structure and flow of international economic activity.
Keywords: E-commerce, global trade, digital platforms, Amazon, Alibaba, Uzum Market, cross-border commerce, global marketplace, data governance, digital logistics, global supply chains, SMEs